(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Token economics determines whether a Web3 protocol thrives or collapses. The design of token supply schedules, staking rewards, fee distribution, liquidity incentives, and governance rights creates a system of economic incentives that shapes every participant’s behaviour – validators secure the network because staking rewards exceed opportunity costs, liquidity providers deposit capital because fee yields exceed competing returns, users pay transaction fees because the service value exceeds the cost, and governance participants vote because token appreciation aligns with protocol improvement. When these incentives are miscalibrated, protocols fail: death spirals (Terra/Luna), unsustainable yield farming (OlympusDAO forks), mercenary capital flight (DeFi Summer liquidity mining), and governance apathy (sub-4% voter turnout across major DAOs). We present the Tokenomics Design Assessment Framework (TDAF), evaluating six incentive mechanism categories – inflationary staking rewards, deflationary fee burns, liquidity mining programmes, vote-escrowed tokenomics, revenue-sharing models, and bonding curve mechanisms – across 18 production protocols with over USD 42 billion in aggregate total value locked. Our Tokenomics Sustainability Score (TSS) measures incentive alignment, capital efficiency, inflation sustainability, value accrual clarity, and resilience to adversarial behaviour. Vote-escrowed tokenomics (Curve-style ve-model) achieves the highest TSS (0.918) by locking tokens for governance weight and directing emissions, creating long-term alignment between token holders and protocol health, while revenue-sharing models achieve the strongest value accrual clarity (0.960).